2006
DOI: 10.2298/sos0602169s
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the structural and optical properties of commercial ZnO powder by mechanical activation

Abstract: Mechanical activation was used as a method for modification of the structural and optical properties of commercial ZnO powder. For this purpose zinc oxide powder was mechanically treated by grinding in a high-energy vibro-mill in a continual regime in air up to 300 minutes. Starting and modified ZnO samples were characterized using XRD, BET and TEM measurements. Optical properties of these samples were investigated by Raman and photoluminescence (PL) spectroscopy. The color of commercial ZnO powder was white w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 1 publication
0
17
0
1
Order By: Relevance
“…The intensity decrease of the most intense second-order Raman mode with NiO addition is accompanied by a redshift (from ∼1154 cm −1 in ZnO down to ∼1140 cm −1 in ZN25) and broadening. The intensity ratio of this mode to the first-order E 1 (LO) mode, I 2LO /I LO , in ZnO and ZN samples can be used to estimate the electron-LO phonon coupling strength [27,28] . The I 2LO /I LO ratio is decreasing with NiO amount from ∼1.92 in ZnO down to ∼1.48 in ZN25 (Fig.…”
Section: Optical Characterization Of Zno/nio Mixturesmentioning
confidence: 99%
“…The intensity decrease of the most intense second-order Raman mode with NiO addition is accompanied by a redshift (from ∼1154 cm −1 in ZnO down to ∼1140 cm −1 in ZN25) and broadening. The intensity ratio of this mode to the first-order E 1 (LO) mode, I 2LO /I LO , in ZnO and ZN samples can be used to estimate the electron-LO phonon coupling strength [27,28] . The I 2LO /I LO ratio is decreasing with NiO amount from ∼1.92 in ZnO down to ∼1.48 in ZN25 (Fig.…”
Section: Optical Characterization Of Zno/nio Mixturesmentioning
confidence: 99%
“…Similar behaviour was observed for undoped zinc oxide powders indicating that the inclusion of lithium ions is not responsible for the spectroscopic changes upon mechanical grinding. A recent study [18] reported a similar decrease in the visible luminescence excited by UV light after grinding experiments and suggested that mechanical grinding induces changes in the defect structure of the zinc oxide crystal lattice. Our results are consistent with these findings but, in addition to the decrease in defect emission, we note the concomitant increase in the band gap emission intensity.…”
Section: Scanning Electron Microscopymentioning
confidence: 56%
“…The grinding time was 30 and 300 minutes and the powders are labeled as ZnO(30) and ZnO(300), respectively. Average crystallite size obtained from X-ray diffraction (XRD) results are: 190 nm for ZnO(0), 106 nm for ZnO(30), and 44 nm for ZnO(300) [2]. Anatase TiO 2 nanopowder was synthesized by laser-induced pyrolysis, using titanium isopropoxide as a liquid precursor.…”
Section: Methodsmentioning
confidence: 99%